2022
DOI: 10.1071/hc22068
|View full text |Cite
|
Sign up to set email alerts
|

They’re sicker than we think: an exploratory study profiling the cardio-metabolic health in a sample of adults with pre-diabetes in Aotearoa New Zealand

Abstract: Introduction. Type 2 diabetes mellitus (T2DM) is a highly prevalent and potentially preventable condition associated with significant health, social, and economic costs. The detection and management of pre-diabetes is an important opportunity to prevent or delay the onset of T2DM and associated morbidities; however, its importance is controversial as the health risks associated with pre-diabetes are poorly understood. Aim. To understand the cardio-metabolic health profile of a sample of adults with pre-diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It is therefore a useful tool in assessing the impact of a dietary intervention on metabolic health (19). In an Aotearoa New Zealand population, the MetSSS positively associated with impaired glucose regulatory status and history of cardiovascular disease for all ethnic groups (20,21). This places it in a good position to have utility as a tool to quantify an individual's cardiometabolic disease risk within the multiethnic population of Aotearoa New Zealand (20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore a useful tool in assessing the impact of a dietary intervention on metabolic health (19). In an Aotearoa New Zealand population, the MetSSS positively associated with impaired glucose regulatory status and history of cardiovascular disease for all ethnic groups (20,21). This places it in a good position to have utility as a tool to quantify an individual's cardiometabolic disease risk within the multiethnic population of Aotearoa New Zealand (20).…”
Section: Discussionmentioning
confidence: 99%
“…The MetSSS has been shown to predict future cardiometabolic disease and can be modified by diet, exercise, and pharmacological intervention to estimate change in cardiometabolic disease risk, and is therefore a useful tool in assessing the impact of a dietary intervention (19). It has been validated in a New Zealand population and has been shown to be responsive to diet and lifestyle interventions in people with pre-diabetes (19)(20)(21).…”
Section: Introduction (Spirit 6a)mentioning
confidence: 99%
“…More than 66% of those with prediabetes who developed CVD or renal disease did not develop T2DM. 25 Our exploratory NZ study 26 found that 74% of a small sample (n = 153) of adults with prediabetes had metabolic syndrome, and there was considerable variability in the severity of this condition. Together, these findings are a timely reminder of the artificial nature of diagnostic cut-off points and the importance of assessing a comprehensive range of risk factors in those with prediabetes.…”
Section: Prediabetes-related Health Outcomesmentioning
confidence: 93%
“…It is therefore a useful tool in assessing the impact of a dietary intervention on metabolic health [ 13 ]. It has been validated in a New Zealand population and has been shown to be responsive to diet and lifestyle interventions in people with pre-diabetes [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%